2017
DOI: 10.1371/journal.pone.0180219
|View full text |Cite
|
Sign up to set email alerts
|

Simulated impacts of ankle foot orthoses on muscle demand and recruitment in typically-developing children and children with cerebral palsy and crouch gait

Abstract: Passive ankle foot orthoses (AFOs) are often prescribed for children with cerebral palsy (CP) to assist locomotion, but predicting how specific device designs will impact energetic demand during gait remains challenging. Powered AFOs have been shown to reduce energy costs of walking in unimpaired adults more than passive AFOs, but have not been tested in children with CP. The goal of this study was to investigate the potential impact of powered and passive AFOs on muscle demand and recruitment in children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…While this study focused on estimating muscle architecture for young, healthy individuals using DTI, this framework could further benefit the musculoskeletal modeling field by measuring similar parameters in pathological populations (e.g. individuals with cerebral palsy [54], muscle atrophy [69], muscular dystrophy [70], and the elderly [71]), whose gait and muscle function are often investigated with biomechanical models and simulations [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…While this study focused on estimating muscle architecture for young, healthy individuals using DTI, this framework could further benefit the musculoskeletal modeling field by measuring similar parameters in pathological populations (e.g. individuals with cerebral palsy [54], muscle atrophy [69], muscular dystrophy [70], and the elderly [71]), whose gait and muscle function are often investigated with biomechanical models and simulations [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…This has potential implications for musculoskeletal modelling in a variety of contexts, such as in clinical studies where gait dynamics of pathological populations are investigated using biomechanical simulations (e.g. cerebral palsy (Rosenberg and Steele, 2017)). Such individuals are generally characterised by a reduction in muscle force‐generating capacity relative to younger individuals (D'Souza et al ., 2019), similar to the elderly generic data set used here.…”
Section: Discussionmentioning
confidence: 99%
“…This has potential implications for musculoskeletal modelling in a variety of contexts, such as in clinical studies where gait dynamics of pathological populations are investigated using biomechanical simulations (e.g. cerebral palsy (Rosenberg and Steele, 2017) (Table 1), where the subject-specific models showed the highest coefficients of all the models through all movements tested. So, while the young generic-based models predicted muscle torques in general to a similar degree of accuracy than the subject-specific models when averaged over all subjects, they were not as consistent at doing so between all individuals.…”
Section: F I G U R Ementioning
confidence: 99%
“…For example, one lower-limb mechanical walking model predicted that an intermediate stiffness in a passive exoskeleton would minimize the energy required to walk, a finding that was later observed experimentally in unimpaired adults [1,14]. More physiologically-detailed musculoskeletal models have been used to predict the impacts of exoskeleton design on muscle activity during walking in children with cerebral palsy and running in unimpaired adults [15,16]. While these studies identified hypothetical relationships between kinematics and the myoelectric impacts of exoskeleton design parameters, their predictions were not evaluated against experimental data.…”
Section: Introductionmentioning
confidence: 99%